2020
DOI: 10.1177/1071100720925426
|View full text |Cite
|
Sign up to set email alerts
|

Operative Treatment for Ganglion Cyst of Flexor Hallucis Longus Sheath

Abstract: Background: Intractable hallucal ganglion cysts (HGCs) are often a symptomatic and recurrent condition. Its connection with the ankle joint is not well understood. Our aim was to evaluate the relationship between tenosynovitis of the flexor hallucis longus (FHL) tendon at the level of the ankle with formation of an HGC. In addition, we sought to analyze the outcomes of cyst excision combined with ankle capsulorrhaphy. Methods: Nineteen patients with HGC who underwent surgical intervention were included between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…In general, recurrence is reported in 33% to 63% of ganglion cysts treated nonsurgically. 7) Between 60% and 95% of ganglion cysts recur after aspiration, while up to 50% recur even after excision. 8 9 10) Optimal surgical outcomes are associated with complete surgical resection, but complete resection does preclude recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, recurrence is reported in 33% to 63% of ganglion cysts treated nonsurgically. 7) Between 60% and 95% of ganglion cysts recur after aspiration, while up to 50% recur even after excision. 8 9 10) Optimal surgical outcomes are associated with complete surgical resection, but complete resection does preclude recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment, considering the ganglion cyst and connections with the underlying pathology of adjacent joints and tendons, is challenging. 5 7) Additionally, complete excision of small ganglion cysts of the toe attached to the overlying thin skin is difficult. Even with complete resection, management through a comprehensive approach to all connections with the ganglion cyst, tendon sheath, and the joint is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using ankle arthrography, Zhang et al demonstrated communication between the ankle or FHL tendon sheath and the cyst in 13 of 19 patients [ 4 ]. They reported no recurrence after the removal of the ganglion cysts and ankle capsulorrhaphy, although the tendon sheath was not directly visualized.…”
Section: Discussionmentioning
confidence: 99%
“…The basic treatment is conservative, including observation, compression, aspiration of cyst fluid, corticosteroid injection, and sclerotherapy, but the recurrence rate is as high as 33% to 63% [ 3 ]. Surgical resection must be chosen when they resist conservative treatment, but the recurrence rate after resection of all foot ganglia is still high, ranging from 5% to 30% [ 4 ]. In this report, we present two cases of persistent hallux ganglion cysts.…”
Section: Introductionmentioning
confidence: 99%